FROM “TRUE STORY” TO MYTH: A SEMIOTIC ANALYSIS OF IDEOLOGICAL CONSTRUCTION IN THE CONJURING: THE DEVIL MADE ME DO IT FILM POSTER - Agustina Indah Bahari; Hendra Aditya; Syahrial Syahrial (Linguists : Journal of Linguistics and Language Teaching, 2026)
This study examined how meaning and ideology were constructed in the film poster of The Conjuring: The Devil Made Me Do It through a semiotic approach. While previous studies on film posters tended to focus on identifying visual and textual signs, limited attention had been given to the analysis of myth and ideological construction, particularly through the integration of Saussure’s and Barthes’ frameworks. Addressing this gap, this study employed a qualitative descriptive method by combining Saussure’s concepts of signifier and signified with Barthes’ levels of signification, denotation, connotation, and myth, to analyze both verbal and non-verbal signs in the poster. The findings revealed that the interaction of visual elements, such as lighting, color, and facial representation, with verbal elements, including the slogan and film title, constructed a layered system of meaning. At the myth level, the poster naturalized specific ideological meanings by reinforcing religious values, legitimizing supernatural authority, and promoting the belief that narratives “based on a true story” were inherently more frightening than fictional ones. This myth operated within a broader ideological context shaped by Western demonological perspectives and reflects the commodification of religious belief within the entertainment industry. This study contributed to semiotic and film studies by offering an integrated analytical framework that combined structural and interpretative approaches. It also provided a critical perspective on how horror film posters functioned as cultural texts that not only represented meaning but also constructed and circulated ideological narratives in contemporary media.